2017
DOI: 10.1186/s40249-017-0293-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of praziquantel on Schistosoma haematobium and re-infection rates among school-going children in the Ndumo area of uMkhanyakude district, KwaZulu-Natal, South Africa

Abstract: BackgroundDespite its low cure rates and possible resistance, praziquantel (PZQ) is the only drug available for schistosomiasis treatment. Hence, monitoring its efficacy is crucial. This study assessed the efficacy of PZQ, determined re-infection and incidence rates of Schistosoma haematobium infection among school-going children in the Ndumo area, KwaZulu-Natal.MethodsA cohort of 320 school-going children (10 – 15 years) in 10 primary schools was screened for S. haematobium infection using the filtration tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
41
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 31 publications
6
41
0
1
Order By: Relevance
“…The findings of this study, which indicated a total reinfection percentage of 10.4% from the two sites suggests that school children living in endemic areas could still be exposed to S. haematobium infection, even after praziquantel treatment. This reinfection percentage (10.4%) corroborates similar work done by Senghor et al [29] and Kabuyaya et al [30], who also reported reinfection rates of 12.6% and 8.1%, respectively. Woldegerima et al [31] also reported a reinfection rate of 13.9%, after 6 months of post-treatment, although this was in S. mansoni.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The findings of this study, which indicated a total reinfection percentage of 10.4% from the two sites suggests that school children living in endemic areas could still be exposed to S. haematobium infection, even after praziquantel treatment. This reinfection percentage (10.4%) corroborates similar work done by Senghor et al [29] and Kabuyaya et al [30], who also reported reinfection rates of 12.6% and 8.1%, respectively. Woldegerima et al [31] also reported a reinfection rate of 13.9%, after 6 months of post-treatment, although this was in S. mansoni.…”
Section: Discussionsupporting
confidence: 91%
“…In the study by Kabuyaya et al [30], the low reinfection percentage observed was associated with the persistent drought throughout their study period. Also, Midzi et al [34] showed that a considerable number of the transmission hotspots (water sources) dried up during their study period, thus limiting the exposure of children to water contact, which might have contributed to the low reinfection percentage.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations